A new species of Philometra (Nematoda: Philometridae) from the sand perch Diplectrum formosum (Serranidae) off Florida, northern Gulf of Mexico - Moravec, František; Bakenhaster, Micah (The Journal of parasitology, 2010)
A new nematode species, Philometra diplectri n. sp. (Philometridae), is described from male and female specimens found in unidentified tissues of head and anterior trunk (males) and subcutaneously in the mouth and under the operculum (females) of sand perch, Diplectrum formosum (Linnaeus) (Serranidae, Perciformes), from the northern Gulf of Mexico off Florida (Florida Middle Grounds). Based on light and scanning electron microscopy examination, the new species differs from other congeners parasitizing the subcutaneous tissues, fins, tissues of the buccal cavity, and gill covers or gill arches of marine and brackish-water fishes, mainly in having 8 conspicuously large cephalic papillae of the external circle, the absence of caudal projections, and the shape and small size of the anterior inflation of the esophagus in gravid females, and in possessing 5 pairs of caudal papillae and spicules 66-78 µm long in males. Philometra diplectri is the first known species of this genus whose gravid females are parasitic in the head tissues of serranid fishes.
Keywords: Microscopy, Electron, Scanning; Spirurida Infections; Prevalence; Dracunculoidea; Percoidea; Bass; Florida; mikroskopie elektronová rastrovací; infekce hlísticemi řádu Spirurida; mužské pohlaví; prevalence; ženské pohlaví; mořská voda; zvířata; Seawater; nemoci ryb; Fish Diseases; Female; Male; Animals